PELET PUPUK ORGANIK DARI RESIDU DIGESTASI ANAEROBIK LIMBAH LUMPUR PABRIK KERTAS (Organic Fertilizer Pellet from Anaerobic Digestion Residue of Paper Mill Sludge Waste) - Rina Susilowati Soetopo; Sri Purwati; Yusup Setiawan; Mukharomah Nur Aini; Aep Surahman; Prima Besty Asthary (JURNAL SELULOSA, 2016)
The study of the organic fertilizer pellet from anaerobic digestion residue of paper mill sludge has been conducted. Study was divided into: characterization of biological sludge, anaerobic digestion process to obtain a precipitate residual sludge, organic fertilizer pellets production, and economic analysis. Pilot scale anaerobic digestion process is done in a paper industry at pH of 5.5 to 6.0, alkalinity of 2000-2500 mg/L and a residence time of 4 days with feed solids content of 0.6%. Stages of organic fertilizer pellets production were dewatering, drying and pellets formation. Pellets were made with a mixture of rice husk ash additive powder of 5-10%. The results showed that the residual sludge from anaerobic digestion process had a solid content (TS) from 2.0 to 4.5%. The process of dewatering of residue sludge and the drying process can increase the levels of solids each up to 26-29% and 80%. Pellets that was produced meets the requirements as organic fertilizer or soil conditioner according to Indonesia National Standard   (SNI) 7847: 2012 that is intended for industrial timber estates (HTI). Based on material balance calculations for industrial scale, biological sludge digestion capacity of 200 tonnes a day with a TS content of 1%, resulting in digestion sludge residue as much as 24 tonnes/ day with a TS content of 3% .From the sludge residue can be made fertilizer pellets with TS of 80.5% as much as 710 kg/day. Economic analysis results indicate that the Pay Back Period was 3.9 years with the Break Even Point (BEP) of 48%.Keywords: anaerobic digestion, biological sludge, sludge residue, organic fertilizer pellet ABSTRAKPenelitian pembuatan pelet pupuk organik dari residu digestasi anaerobik lumpur biologi industri kertas telah dilakukan. Tahapan penelitian terdiri dari karakterisasi lumpur biologi, digestasi anaerobik untuk memperoleh endapan residu lumpur, pembuatan pelet pupuk organik, dan analisis tekno ekonomi. Proses digestasi anaerobik skala pilot dilakukan di industri kertas pada pH 5,5 – 6,0, alkalinitas 2000 - 2500 mg/L, dan waktu tinggal 4 hari dengan kadar padatan total (TS) umpan 0,6%. Tahapan pembuatan pelet pupuk organik meliputi penghilangan air, pengeringan dan pembentukan pelet. Pembuatan pelet dilakukan dengan menambahkan aditif abu sekam 5-10 %. Hasil penelitian menunjukkan bahwa residu lumpur dari proses digestasi anaerobik mengandung kadar padatan total 2,0 - 4,5%. Proses penghilangan air pada residu lumpur dan pengeringannya dapat meningkatkan kadar padatan berturut-turut 26 – 29% dan 80%. Pelet yang dihasilkan memenuhi persyaratan sebagai pupuk organik atau pembenah tanah menurut SNI 7847:2012 yang diperuntukkan untuk Hutan Tanaman Industri (HTI). Berdasarkan perhitungan neraca massa skala industri, digestasi anaerobik dengan umpan lumpur biologi 200 ton/hari dan kadar padatan total (TS) 1% menghasilkan residu lumpur 24 ton/hari dengan TS 3%. Residu lumpur tersebut dapat dibuat menjadi 710 kg pelet pupuk organik/hari dengan TS 80,5%. Hasil analisis ekonomi menunjukkan bahwa lamanya investasi kembali adalah 3,9 tahun dengan titik pulang pokok 48%.Kata kunci: digestasi anaerobik, lumpur biologi, residu lumpur, pelet pupuk organik